Observation of the decay Λ0b→ψ(2S)pπ− - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; De Cian, Michel; Comerma-Montells, Albert; Dordei, Francesca; Esen, Sevda; Gerick, David; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kecke, Matthieu; et al. (Journal of high energy physics, 2018)
The Cabibbo-suppressed decay Λ b 0 → ψ(2S)pπ− is observed for the first time using a data sample collected by the LHCb experiment in proton-proton collisions corresponding to 1.0, 2.0 and 1.9 fb−1 of integrated luminosity at centre-of-mass energies of 7, 8 and 13 TeV, respectively. The ψ(2S) mesons are reconstructed in the μ+μ− final state. The branching fraction with respect to that of the Λ b 0 → ψ(2S)pK− decay mode is measured to be B(Λ0b→ψ(2S)pπ−)B(Λ0b→ψ(2S)pK−)=(11.4±1.3±0.2)%,B(Λb0→ψ(2S)pπ−)B(Λb0→ψ(2S)pK−)=(11.4±1.3±0.2)%, \frac{\mathrm{\mathcal{B}}\left(Λ_{b}^0→ \uppsi \left(2S\right){p\uppi}^{-}\right)}{\mathrm{\mathcal{B}}\left(Λ_{b}^0→ \uppsi \left(2S\right){pK}^{-}\right)}=\left(11.4± 1.3± 0.2\right)%, where the first uncertainty is statistical and the second is systematic. The ψ(2S)p and ψ(2S)π− mass spectra are investigated and no evidence for exotic resonances is found. Open image in new window
Im Titel werden "lambda" und "psi" als griechische Buchstaben dargestellt
Im Titel sind "0" und "b" untereinander geschrieben: "0" hochgestellt, "b" tiefgestellt
The LHCb collaboration: R. Aaij, P. d'Argent, S. Bachmann, S. Braun, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, D. Gerick, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, A. Piucci, M. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere]
Gesehen am 28.05.2019